Odpowiedzi

2009-09-06T17:53:14+02:00
1/x+1/y=1/f /*f
(1/x+1/y)*f=1 /:(1/x+1/y)
f=1/(1/x+1/y)

1/x+1/y=1/f /-(1/y)
1/x=1/f-1/y /*x
1=1/f-1/y*x /:(1/f-1/y)
x=1/(1/f-1/y)

1/x+1/y=1/f /-(1/x)
1/y=1/f-1/x /*y
1=1/f-1/x*y /:(1/f-1/x)
y=1/(1/f-1/x)

1 5 1
  • Użytkownik Zadane
2009-09-06T17:58:27+02:00
1/x + 1/y = 1/f
najpierw x
1/x + 1/y = 1/f //-1/y
1/x=1/f-1/y //*x
1=x(1/f-1/y)//:(1/f-1/y)
x=1/(1/f-1/y)
teraz y:
1/x + 1/y = 1/f //-1/x
1/y=1/f-1/x //*y
1=y(1/f-1/x)//:(1/f-1/x)
y=1/(1/f-1/x)
na koniec f:
1/x + 1/y = 1/f//*f
f(1/x + 1/y )=1//:(1/x + 1/y )
f=1/(1/x + 1/y )
pozdrawiam dagmara
4 4 4